The «suitability» criteria implemented on the migrant’s housing rights: a changeable geometry - Encarnación La Spina, Encarnación (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The universal scope of the suitable concept and the minimal content of housing rights has been developed by the Committee on Economic, Social and Cultural Rights. However, such a concretion, considering the Spanish case, has been implemented from a changeable dimension. On the one hand, the juridical irresolution of suitability criterion has been solved according to technical indicators and, on the other, under the migratory context , such parameters have been extended according to the administrative situation and the aim of the entrance. This paper tries to point out the underlying controversies on the scope of the criterion when the immigrant is accepted as a productive element (guest workers) or as a reproductive element (head of household). In the first case, the right to housing is not only limited or denied; the absence of a suitable housing is even tolerated. In the second case, this right is subject to rules of the family reunification process
Keywords: Migrant; Housing Rights; Spanish Migration Law; International human rights law; Suitable housing; Guest workers; Head of Household